124 Feasibility of Spinal Motor Mapping Using High-resolution Spinal Cord Stimulation Paddles in Patients with Chronic Pain. (1st April 2022) - Telkes, Ilknur; Hadanny, Amir; DiMarzio, Marisa D.; Chitnis, Girish; Staudt, Michael D.; Paniccioli, Steven; O'Connor; Rachael Grey, Katherine; Gillogly, Michael; Khazen, Olga; McLaughlin, Bryan; Pilitsis, Julie G.
Abstract : INTRODUCTION: High-resolution spinal cord stimulation (HR-SCS) paddles, which have the ability to target both medially and laterally oriented spinal targets (dorsal columns and dorsal horns respectively), may provide improved options for treating chronic pain. The physical rigidity of existing technologies often either precludes lateral placement due to compression of nerve roots or lacks the ability to concurrently stimulate the medial targets. METHODS: During standard of care SCS placement, intraoperative neuromonitoring (IONM) recordings were performed with the HR-SCS paddle. Spinal motor mapping was performed at 18 muscle groups at 60 Hz/300 µs at increasing amplitudes from 0-to-10 mA. EMGs were acquired by Cadwell CascadePro IONM system and analyzed in MATLAB. For feature extraction, root-mean-square values of denoised EMGs were computed and normalized to baseline (stimulationOFF). Data from left and right sided data were not significantly different (p > 0.05) and combined for analysis. RESULTS: Electrophysiological signals were recorded in twelve subjects (7 women) with chronic pain. The testing was performed between T9-12 depending on the patients' trial response. Based on overlayed images of HR-SCS paddles, all contacts were aligned with respect to anatomical midline (in one case, to electrophysiological middle). Distribution of EMGs above 50% change revealed stronger responses in adductor magnus, medial gastrocnemius (MG), and tibialis anterior (TA) when stimulation was delivered from the lateral contacts. Responses were higher in gluteus maximus when stimulation was delivered from the medial contacts. Statistical analysis showed significance difference between contacts in MG (p = 0.041) while it was marginal in TA (p = 0.072). Laterality was not observed in the abdominal muscles in either condition. CONCLUSION: By using our routine IONM setup and offline signal processing techniques, we showed that the HR-SCS paddle with 8-columns was able to trigger distinct motor responses at thoracic levels of T9-12 in 12 subjects in accordance with the dorsal column fibers spatial organization.